A survey on the educational tour planning among the studentsof diploma in tourism management in the polytechnic - Jaafar, Norasmah (2003)
The study of "A S urvey on The Educational Tour Planning Among The Students of Diploma in Tourism Management in The Polytechnic" aim to assess the students' needs for the tour planning's guide. The study is developing on the contribution and the importance of the ETP as one of the effective methods in teaching and learning of tourism study. It is to provide the student with experience and technical training about tourism activities and process. ETP also hopes to strengthens the student understanding toward the subject learn in the tourism study. In order to assess the student's needs on the Educational Tour Planning guide, the study had produced a similar ETP guide in the form of booklets to be tested during the study. The project study involved several steps in order to be completed. It is such as the formulation of the problem, the review of the literature, the formulation of the study methodology, the production of the ETP Guidebook, field survey and finally the analyses and discussion made on the data gathered during the study. The survey involves 100 respondents among the students of Diploma in Tourism Management in the Polytechnic. Through the findings, the study indicates that the current tested product is acceptable among the students of Diploma in Tourism Management in the Polytechnic as a guide to plan for the tour. The findings also shows a slight different between the respondents who are using the ETP Guidebook and those who are not in the basis of their ETP results. Due to the important of the study, the researcher hopes to be having a fair discussion and excellence recommendation for the development of the product regarding to the current study. This report writing also important to provide a written reference for the future related study.